Der Altstädter Ring in Prag als zentraler Ort städtischer und nationaler Geschichte. - Svatosová, Hana (Deutsches Institut für Urbanistik, 2019)
In drei Abschnitten schildert die Autorin Geschichte und Funktionen des Altstädter Rings: Funktionen des Altstädter Rings in Mittelalter und Früher Neuzeit; Der Altstädter Ring als Beispiel der kaiserzeitlichen Modernisierung Prags und Ort der Tschechoslowakischen Republik im 19. und 20. Jahrhundert; Zwischen historischer Erinnerung und kommerzieller Ausbeutung: Der Altstädter Ring nach November 1989.

The Old Town Square is one of the psychologically most sensitive places in Prague and the whole country, the scene of socio-political events that have entered the collective memory of the local population. From the Middle Ages, the square served as a meeting place for the town's inhabitants and for the representative activities of the local society and, from the second half of the 19th century, of the Czech national society. The essay sketches the role of the square in urban and national life in the 19th and 20th centuries In relation to the turbulent social and political developments in Bohemia and Central Europe. lt is also dedicated to the urban, architectural and artistic changes of the square, which were often closely connected with urban and national politics. After the political upheaval in 1989, the square became the scene of many actions of all kinds and the object of entrepreneurial, commercial interests. The city administration does not really know what to do with the square and its interest is oriented towards other squares in the city.
Keywords: Stadtgeschichte; Stadtplatz; Rathausplatz; Historischer Platz; Öffentlicher Raum; Symbolgehalt; Politik; Öffentlichkeit; Lokale Identität; Nation